Gambaran Epidemiologi Anak dengan Infeksi Dengue Berat di RSUD Dr. Soetomo - Fadilla, Aulia Nur; Husada, Dominicus; Utomo, Budi (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Introduction: Dengue infection is endemic to Indonesia and remains a public health problem. Severe dengue infection can cause rapid death, especially in children. Aim: To determine the epidemiology of children with severe dengue infection in Dr. Soetomo Hospital. A cross-sectional study was conducted at the pediatric ward of Dr. Soetomo Hospital. Data were derived from medical records of children aged ≤18 years which hospitalized with severe dengue from March to April 2019. Of 135 children admitted with DHF, obtained 48 samples with characteristics greater than 5–12 years old (72.9%), male (58.3%), residence Surabaya (89.6%), elementary school (60.3%), referral (81.3%), hospitalized ≤5 days (66.7%), day of illness ≥4 days (89.6%), moderate malnutrition (35.4%), had severe plasma leakage consisting of DHF grade III (73%) and IV (27%). Two patients died (4.2%). No patient with congenital disease and malignancy. This study is not in line with the tendency of shifted dengue incidence to older age groups (greater than15 years old) in Indonesia. All patients had severe plasma leakage. No severe dengue patient with severe hemorrhage and organ impairment. Most patients were male, had moderate malnutrition, from referral, day of illness ≥4 days, hospitalized ≤5 days.